PRESENTATION AND DIAGNOSIS OF ALLERGIC FUNGAL SINUSITIS - ullah, Zakir; Nawaz, Ghareeb; Sattar, Syed Fazle (Journal of Ayub Medical College Abbottabad, 2010)
Background: Allergic fungal sinusitis (AFS) is a form of fungal disease that has recently been considered a distinct clinicopathologic entity. Other forms of fungal sinusitis include acute-fulminant (invasive), chronic indolent (invasive) and mycetoma (non-invasive). Objectives were to assess the presentation and to describe the diagnostic techniques for allergic fungal sinusitis in our setup. Method: Descriptive study was conducted in the Department of ENT and Head & Neck Surgery, Khyber Medical College and Khyber Teaching Hospital, Peshawar from January 2002 to April 2008. Twenty-three cases of allergic fungal sinusitis (ASF) were selected for the study. Data like, name, age, sex, address, clinical features, labs (Eosinophil count) and imaging studies (CT and/or MRI) were recorded, including the pre- and postoperative treatment, operative findings and postoperative results, recurrence of disease were also recorded. Surgical procedures were performed on all cases followed by medical treatment. Results: Study revealed that AFS is a disease of younger age, mainly occurring in 2nd & 3rd decade of life, with male to female ratio 1:1.3. Allergic rhinitis (91%) and nasal polyposis (91%) were important associated factors. Nasal obstruction (96%), nasal discharge (91%), post-nasal discharge (87%) and unilateral multi sinus extension were important clinical features. Increased eosinophil count and increased IgE level was found in 78% cases. Histopathological analysis showed fungal hyphae in all cases and aspergillus was predominant organism on culture. Orbital erosion was seen in 78% and skull base erosion was observed in 9%. Recurrence of disease was seen in nine cases. Conclusion: Allergic fungal sinusitis (AFS) is a disease of young immunocompetent adults. Nasal obstruction, nasal discharge, nasal allergy and proptosis were the most common presentations. Initial diagnosis of allergic fungal sinusitis requires high index of suspicion in patients presenting with chronic rhinosinusitis, such cases should be properly evaluated. Differentiation from invasive forms of fungal sinus disease is crucial. Keyword: Sinusitis, Allergic Fungal Sinusitis, Skull base erosion, Orbital erosion, Fungal